2016
DOI: 10.1177/1535370216632623
|View full text |Cite
|
Sign up to set email alerts
|

Id-1, Id-2, and Id-3 co-expression correlates with prognosis in stage I and II lung adenocarcinoma patients treated with surgery and adjuvant chemotherapy

Abstract: Inhibitors of DNA binding/inhibitors of differentiation (Id) protein family have been shown to be involved in carcinogenesis. However, the roles of Id during lung adenocarcinoma (ADC) progression remain unclear. Eighty-eight ADC samples were evaluated for Id-1,2,3 level and angiogenesis (CD 34 and VEGF microvessel density) by immunohistochemistry and morphometry. The impact of these markers was tested on follow-up until death or recurrence. A significant difference between tumor and normal tissue was found for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Id1 promotes carcinogenesis and metastasis, and predicts prognosis of non-small cell lung cancer (NSCLC). Study shows that Id1 and Id3 co-expression is associated with a poor clinical outcome in patients with locally advanced NSCLC [19,20]. In analysis of 532 NSCLC patients' samples, Id1 was found significantly correlated with EMT-related proteins and it enables the tumor and the microenvironment to colonize the liver.…”
Section: Lung Cancermentioning
confidence: 97%
“…Id1 promotes carcinogenesis and metastasis, and predicts prognosis of non-small cell lung cancer (NSCLC). Study shows that Id1 and Id3 co-expression is associated with a poor clinical outcome in patients with locally advanced NSCLC [19,20]. In analysis of 532 NSCLC patients' samples, Id1 was found significantly correlated with EMT-related proteins and it enables the tumor and the microenvironment to colonize the liver.…”
Section: Lung Cancermentioning
confidence: 97%
“…The inhibitor of DNA binding (Id) protein includes Id1, Id2, Id3, and Id4 members, function as inhibitors of basic helix-loop-helix (bHLH) transcription factors [10]. As vital regulators of cell cycle, cell growth and differentiation, Id proteins are increasingly observed involving in various tumor-related processes, such as chemotherapeutic drug resistance [11], stem cell features [12], metabolic reprogramming [13], EMT [14], angiogenesis and metastasis [15]. However, studies about the role of Id proteins in ESCC were limited, especially for Id3.…”
Section: Ivyspringmentioning
confidence: 99%
“…[1][2][3] Its overexpression is closely correlated to the occurrence, development, and prognoses of many malignant tumors such as lung cancer, gastric cancer, pancreatic cancer, and cervical cancer. 4 A previous study has suggested that the overexpression of Id-1 is closely correlated to occurrence and development of colorectal cancer. 5 However, there are no detailed reports on its corresponding proliferation in vitro and invasion experiments.…”
Section: Introductionmentioning
confidence: 97%
“…This gene can promote cell proliferation, induce the generation of blood vessel endothelia with tumors, and promote tumor growth and invasion . Its overexpression is closely correlated to the occurrence, development, and prognoses of many malignant tumors such as lung cancer, gastric cancer, pancreatic cancer, and cervical cancer . A previous study has suggested that the overexpression of Id‐1 is closely correlated to occurrence and development of colorectal cancer .…”
Section: Introductionmentioning
confidence: 99%